Altered Fecal Microbiota Signatures in Patients With Anxiety and Depression in the Gastrointestinal Cancer Screening: A Case-Control Study - Zhu, Juan; Li, Minjuan; Shao, Dantong; Ma, Shanrui; Wei, Wenqiang (Frontiers in Psychiatry, 2021)
Background: Increasing attention has been devoted to cancer screening and microbiota in recent decades, but currently there is less focus on microbiota characterization among screeners and its relationship to anxiety and depression. Methods: We characterized the microbial communities of fecal samples collected through the FOBT card from anxiety and depression screeners and paired controls in Henan, China (1: 2, N=69). DNA was extracted using the MOBIO PowerSoil kit. The V4 region of the 16S rRNA gene was sequenced using MiniSeq and processed using QIIME1. LEfSe was used to identify differentially abundant microbes, the Wilcoxon rank-sum test was used to test alpha diversity differences, and permutational multivariate analysis of variance was used to test for differences in beta diversity. Results: Similar fecal microbiota signatures in composition were found among screeners. The intestinal microbial environments by phylum were all composed primarily of Firmicutes, Bacteroidetes and Proteobacteria, and the corresponding top genera were Faecalibacterium, Roseburia and Prevotella. Compared with controls, the ranking of the top 5 genera in the anxiety and depression group changed, and the dominant genus was Prevotella in the anxiety and depression group and Faecalibacterium in the control group. There was a lower relative abundance of Gemmiger (1.4% vs. 2.3%, P=0.025), Ruminococcus (0.6% vs. 0.8%, P=0.037) and Veillonella (0.6% vs. 1.3%, P=0.020). This may be linked to the lower alpha diversity in participants with anxiety and depression (Observed OTUs: 122.35 vs. 143.24; Chao1: 127.35 vs. 149.98), although no significant differences were observed. Distinct clustering in microbial composition between the two groups was detected for the Jaccard distance (P=0.011). Conclusions: Our study showed differing microbial characterization among participants with anxiety and depression in the endoscopic screening of upper gastrointestinal cancer. Gemmiger, Ruminococcus and Veillonella were informative and have potential clinical implications, which need to be confirmed by large-scale, prospective cohort studies and biological mechanism research.